2015
DOI: 10.1002/mpr.1473
|View full text |Cite
|
Sign up to set email alerts
|

Predicting disability pension – depression as hazard: a 10 year population‐based cohort study in norway

Abstract: Disability pension (DP) is an escalating challenge to individuals and the welfare state, with mental health problems as imminent hazard. The objective of the present paper was to determine if a diagnosis of depression increased the risk of subsequent DP, and whether the risk differed by gender. A population cohort of 1230 persons were diagnostically interviewed (Composite International Diagnostic Interview, CIDI) in a population study examining mental health, linked to the DP registry and followed for 10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…The findings that peer problems and hyperactivity in females were associated with being NEET-later, is supported by previous findings in the NAAHS study among young females when it comes to high school dropout31 and partly for tertiary education 30. Myklestad et al 69 suggest that poor mental health contributes to high school dropout or lower educational achievement,30 31 and later work marginalisation by disability pension 70. SDQ’s hyperactivity scale used in this study also includes attention problems, which are shown to cause cognitive problems in school 71.…”
Section: Discussionsupporting
confidence: 66%
“…The findings that peer problems and hyperactivity in females were associated with being NEET-later, is supported by previous findings in the NAAHS study among young females when it comes to high school dropout31 and partly for tertiary education 30. Myklestad et al 69 suggest that poor mental health contributes to high school dropout or lower educational achievement,30 31 and later work marginalisation by disability pension 70. SDQ’s hyperactivity scale used in this study also includes attention problems, which are shown to cause cognitive problems in school 71.…”
Section: Discussionsupporting
confidence: 66%
“… 36 Gender-stratified analyses show that impacts of depression and/or CMDA on disability pension were higher among men. 33 , 35 , 36 An increased risk of disability pension among women with anxiety was noted, but the impact was small in relation to the consequences of depression and CMDA, and gender interaction effects were non-significant. However, in a Finnish sample of depressed individuals, male gender was associated with lower disability pension rates at 18 months follow-up 32 while gender was non-significant at five years follow-up.…”
Section: Resultsmentioning
confidence: 96%
“…Studies have reported that 17-22% of patients with depression are eventually granted a disability pension, [7][8][9][10] and the risk of obtaining a disability pension is 2-3 times higher in employees with severe depressive symptoms compared with the background population. 11,12 Years of work lost have, to our knowledge, not been estimated for individuals with depression, but one study showed that people who receive disability pension due to mood disorders lose around 15 years of work, assuming a scheduled retirement age of 67 years. 13 Studies have shown that young age at depression onset, disease severity, duration and number of previous depression episodes, psychiatric and somatic comorbidity, as well as low educational level contribute to risk of early workforce exit.…”
Section: Early Labor Force Exits In Patients With Treatment-resistantmentioning
confidence: 99%